2015
DOI: 10.1002/2015gl065804
|View full text |Cite
|
Sign up to set email alerts
|

A strong seasonal dependence in the Martian hydrogen exosphere

Abstract: Hubble Space Telescope and Mars Express observed unexpected rapid changes in the Martian hydrogen exosphere involving a decrease in scattered Lyman α intensity in fall 2007 (solar longitude, Ls = 331°–345°). These changes detected were speculated to be a combination of seasonal variation and/or dust storms and lower atmospheric dynamics. Here we present Hubble Space Telescope observations of Mars in 2014 over a broad range of heliocentric distances and seasons (Ls = 138°–232°) which indicate a factor of ~3.5 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
119
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(142 citation statements)
references
References 50 publications
18
119
0
5
Order By: Relevance
“…A neutral H, H 2 , and O Chamberlain (1963) exosphere is generated (Halekas, 2017) using exobase densities and temperatures of 1 × 10 6 cm −3 and 300 K, respectively, values that are in agreement with previously reported observations (e.g., Anderson & Hord, 1971;Bhattacharyya et al, 2015;Chaufray et al, 2008;Chaffin et al, 2015;Feldman et al, 2011). A neutral H, H 2 , and O Chamberlain (1963) exosphere is generated (Halekas, 2017) using exobase densities and temperatures of 1 × 10 6 cm −3 and 300 K, respectively, values that are in agreement with previously reported observations (e.g., Anderson & Hord, 1971;Bhattacharyya et al, 2015;Chaufray et al, 2008;Chaffin et al, 2015;Feldman et al, 2011).…”
Section: Simulations Of Charge Exchange In the Upstream Regionsupporting
confidence: 88%
“…A neutral H, H 2 , and O Chamberlain (1963) exosphere is generated (Halekas, 2017) using exobase densities and temperatures of 1 × 10 6 cm −3 and 300 K, respectively, values that are in agreement with previously reported observations (e.g., Anderson & Hord, 1971;Bhattacharyya et al, 2015;Chaufray et al, 2008;Chaffin et al, 2015;Feldman et al, 2011). A neutral H, H 2 , and O Chamberlain (1963) exosphere is generated (Halekas, 2017) using exobase densities and temperatures of 1 × 10 6 cm −3 and 300 K, respectively, values that are in agreement with previously reported observations (e.g., Anderson & Hord, 1971;Bhattacharyya et al, 2015;Chaufray et al, 2008;Chaffin et al, 2015;Feldman et al, 2011).…”
Section: Simulations Of Charge Exchange In the Upstream Regionsupporting
confidence: 88%
“…Interestingly, observational evidence of a strong seasonal dependence in the hydrogen exosphere of Mars has been recently reported in Clarke et al [], Chaffin et al [], and Bhattacharyya et al [], based on Hubble Space Telescope and MEX scattered Lyman α brightness observations. In agreement with these observations, a large decrease in the median penetrating proton density [ Halekas et al , ] derived from MAVEN Solar Wind Ion Analyzer (SWIA) [ Halekas et al , ] measurements is observed during the MAVEN mission (lower density values for larger heliocentric distances) and also indicates a high level of seasonal variability in the Martian H exosphere.…”
Section: Discussionmentioning
confidence: 94%
“…Consequently, Yamauchi et al [] concluded that even though the variation in solar UV flux has a major effect on the formation of pickup ions, it is not the only contributing component. Similarly, Bhattacharyya et al [] also concluded that the observed seasonal changes in the neutral H exospheric densities cannot be explained only on the basis of changes in the incident EUV flux. Moreover, the supplying process of H to the exosphere of Mars through diffusion of molecular H 2 from lower altitudes is slow, not capable of explaining observed short‐term changes in the H density.…”
Section: Discussionmentioning
confidence: 99%
“…SWIA observations also confirm a strong seasonal variation of the hydrogen corona [ Yamauchi et al ., ; Chaffin et al ., ; Bhattacharyya et al ., ], with much larger (an order of magnitude) amplitude than the heliocentric variation in EUV input. A longer baseline of observations afforded by additional MAVEN extended missions could reveal a solar cycle component to the hydrogen variability or interannual variations in the seasonal variation of the hydrogen corona.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure (third panel), the charge exchange rate upstream of the shock must vary with time, since we observe a large decrease in the median penetrating proton density over the MAVEN mission, in addition to the expected solar wind variability. This decline most likely primarily reflects changes in the Martian exosphere, which we know to have a high degree of seasonal variability, thanks to spectroscopic observations [ Chaffin et al ., ; Bhattacharyya et al ., ] and pickup ion measurements [ Yamauchi et al ., ]. Given the results of Kallio et al .…”
Section: Solar Energy Inputs To the Martian Systemmentioning
confidence: 98%